2018
DOI: 10.1108/jcom-10-2017-0114
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of message frames on information seeking and processing

Abstract: Purpose The purpose of this paper is to apply the situational theory of publics and framing theory in the context of environmental corporate social responsibility (CSR) communication research to determine how message frames impact information seeking and processing. Design/methodology/approach Using a 3 (message frame: diagnostic, prognostic, or motivational) × 2 (environmental issue: general vs specific) plus control between subjects experimental design, the study examines the attitudes, cognitions, and beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Findings from this study indicated that individuals that fall under public categories that seek information are impacted differently than those who simply process information that may be presented to them. This finding is significant as it provides both researchers and practitioners guidance regarding differences in behavioral intention between the types of publics (Overton, 2018). In addition, it confirmed the applicability of the theoretical framework when applying it to polarizing topics such as environmental issues.…”
Section: Theoretical Frameworksupporting
confidence: 58%
See 4 more Smart Citations
“…Findings from this study indicated that individuals that fall under public categories that seek information are impacted differently than those who simply process information that may be presented to them. This finding is significant as it provides both researchers and practitioners guidance regarding differences in behavioral intention between the types of publics (Overton, 2018). In addition, it confirmed the applicability of the theoretical framework when applying it to polarizing topics such as environmental issues.…”
Section: Theoretical Frameworksupporting
confidence: 58%
“…Grunig (1983) found that identifying differences in types of publics could aid in developing more effective and targeted communication efforts. The theory proposes that publics arise based on issues that affect them and can assist communication professionals with determining when, why, and how people seek information; their responsiveness to issues; and how communication impacts cognitions, attitudes, and behavior (Overton, 2018). It has been found that the relationship among the variables in STP may explain how people develop attitudes, cognitions, and behaviors.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations